Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1109/tits.2018.2883823
|View full text |Cite
|
Sign up to set email alerts
|

Driver Drowsiness Detection Using Condition-Adaptive Representation Learning Framework

Abstract: We propose a condition-adaptive representation learning framework for the driver drowsiness detection based on 3D-deep convolutional neural network. The proposed framework consists of four models: spatio-temporal representation learning, scene condition understanding, feature fusion, and drowsiness detection. The spatio-temporal representation learning extracts features that can describe motions and appearances in video simultaneously. The scene condition understanding classifies the scene conditions related t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 53 publications
0
46
0
Order By: Relevance
“…To fully model the problem of the complex correlation between two modal features in the process of computer vision tasks, Hong et al [26] observed that the correlation between related features can be captured using the element-wise multiplication interaction between the feature maps. Therefore, Yu et al [27] fused the spatio-temporal feature representation obtained from 3D-DCNN with the related scene annotation by element-wise multiplication interaction, and added a set of conditional adaptive representation to effectively distinguish driver drowsiness.…”
Section: Related Workmentioning
confidence: 99%
“…To fully model the problem of the complex correlation between two modal features in the process of computer vision tasks, Hong et al [26] observed that the correlation between related features can be captured using the element-wise multiplication interaction between the feature maps. Therefore, Yu et al [27] fused the spatio-temporal feature representation obtained from 3D-DCNN with the related scene annotation by element-wise multiplication interaction, and added a set of conditional adaptive representation to effectively distinguish driver drowsiness.…”
Section: Related Workmentioning
confidence: 99%
“…To learn discriminative features which cover both the complexity and the diversity of human actions, we attempted a joint learning method for motion and appearance based on the convolutional neural network. Fusing of multiple data is a commonly used approach in visual recognition studies for scene segmentation [56], [57], object detection [58], and event detection [59]- [61]. In recent action recognition studies [50]- [53], several have reported that using multiple information can provide better action recognition performance than using a single data type only.…”
Section: A Joint Spatio-temporal Representation Extractionmentioning
confidence: 99%
“…α, C andā are the extracted joint ST-representation, the number of action classes in the training dataset and the given label corresponding to an input video, respectively. This combining loss function is a commonly used approach in various visual recognition studies [61], [68], [69]. According to [68], the center loss, which simultaneously learns the center for the deep features of each class and penalizes the distances between the deep features and their corresponding class centers, showed better performance than conventional loss functions such as softmax loss.…”
Section: Outputmentioning
confidence: 99%
“…This method showed a classification accuracy of 92.33%. Likewise [12], introduces an adaptive conditional representation learning system for driver drowsiness detection based on a 3D-CNN. The proposed system consists of four steps (spatio-temporal representation, data preprocessing, features combination and somnolence detection).…”
Section: Introductionmentioning
confidence: 99%